When Should I Call You? An Analysis of Differences in Demographics and Responses According to Respondents' Location in a Mobile CATI Survey. (December 2015) - Vicente, Paula; Lopes, Inês
Mobile phones are increasingly being used to collect social and marketing data, and some say it is just a question of time before they replace fixed phones. Although there is some evidence that much of the knowledge on computer-assisted telephone interviewing (CATI) surveys can be applied to mobile CATI surveys, the specificities of mobile communications must be given due consideration in the design and procedures for surveys using mobile phones. This study investigates whether the location of the respondent at the time of the interview—at home or outside the home—affects sample composition and responses in a mobile CATI survey. Although findings reveal several significant distinctions between the demographic characteristics of at-home and outside-home respondents, namely, sex, age, educational level, professional status, and the major contributor to household income, only a few differences were found in responses to behavioral and attitudinal items.